Rhetorical move structure of soft and hard science research article introductions by novice Indonesian authors - Nabilla, Salma; Kurniawan, Eri; Gunawan, Wawan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2021)
Research article introduction is crucial in justifying a research topic and presenting the significant contribution of a study to the advancement of knowledge. Prior studies have attempted to investigate research article introductions from various viewpoints. However, the way novice Indonesian authors rhetorically construct their introductions is still under-explored. This study aims to explore cross-disciplinary introductions with regard to rhetorical move structure and the linguistic realizations of the moves. Employing Swale’s (2004) revised CARS model, a corpus of 10 research articles from the fields of soft and hard science were analyzed. The findings revealed that the two disciplines were in agreement on the compulsory status of Move 1 Establishing a territory and Move 3 Presenting the present work and the conventional use of Move 2 Establishing a niche. However, discrepancies arose in the step level. Regarding the linguistic features, soft and hard science authors preferred using present tense and active voice in realizing the moves. In addition, a considerable number of metadiscourse such as hedges and boosters were observed in the introductions. This study concludes that novice Indonesian authors’ disciplinary expertise possibly influences the quality of their introductions. Pendahuluan artikel penelitian sangat penting dalam menjustifikasikan topik penelitian dan menyajikan kontribusi signifikan dari studi yang dilakukan untuk perkembangan ilmu pengetahuan. Penelitian terdahulu telah berupaya untuk menyelidiki bagian pendahuluan artikel penelitian dari beragam perspektif. Namun, cara penulis pemula Indonesia mengkonstruksi bagian pendahuluan mereka secara retoris masih kurang dieksplorasi. Studi ini bertujuan untuk mengeksplorasi bagian pendahuluan lintas disiplin berkaitan dengan struktur pola retorika pendahuluan dan realisasi linguistik dari pola tersebut. Menerapkan revisi model CARS oleh Swales (2004), sebuah korpus yang merupakan kumpulan 10 pendahuluan artikel penelitian dari disiplin ilmu soft dan hard science dianalisis. Temuan penelitian menunjukkan bahwa kedua disiplin sepakat tentang status wajib dari Move 1 Establishing a territory dan Move 3 Presenting the present work, dan penggunaan konvensional Move 2 Establishing a niche. Namun, perbedaan muncul pada tiap tingkatan. Berkaitan dengan fitur linguistik, penulis soft dan hard science lebih memilih menggunakan kalimat aktif dan bentuk waktu masa kini (present tense) dalam merealisasikan pola. Selain itu, sejumlah besar metadiscourse seperti hedges dan boosters teramati dalam bagian pendahuluan. Studi ini menyimpulkan bahwa perbedaan fokus keilmuan penulis pemula Indonesia kemungkinan mempengaruhi kualitas pendahuluan mereka.